Proposing Feminist Intepretation of The Qur'an and Affirmative Policy to Suport Women Leadership In Indonesian State Islamic Higher Education - Nina Nurmila (Musawa Jurnal Studi Gender dan Islam, 2020)
Religion can be supportive or discriminative toward women depending on how we interpret religion. When religion is interpreted from patriarchal lenses, it tends to be discriminative toward women, such as in the case of women leadership. This paper will challenge the existing mainstream patriarchal interpretation of the Qur’an on women leadership by offering new feminist interpretation of the Qur’an which is friendly to women and suggesting affirmative policy to increase the number of women leaders in State Islamic Higher Education (Perguruan Tinggi Keagamaan Islam Negeri/PTKIN). This paper uses feminist methodology by using interview and literature studies as methods of data collection. This study shows that leadership in PTKIN is still dominated by men due to the strong patriarchal culture. There are only seven female rectors out of 58 PTKIN in Indonesia. Based on this finding, the new interpretation of the Qur’an which is friendly to women needs to be promoted and the existing gender-neutral policy on the selection of rector in PTKIN needs to be revised into affirmative policy to allow more rooms for women’s leadership to achieve Planet 50-50 by 2030. [Agama itu bisa bersifat mendukung atau diskriminatif terhadap perempuan tergantung pada bagaimana kita menafsirkan agama, misalnya dalam hal kepemimpinan perempuan. Artikel ini akan mengkritisi penafsiran Al-Qur’an tentang kepemimpinan perempuan yang ada yang pada umumnya bersifat patriarki dengan menawarkan penafsiran feminis yang baru tentang Al-Qur’an, yang ramah terhadap perempuan, dan dengan menyarankan adanya kebijakan afirmatif untuk meningkatkan jumlah pemimpin perempuan di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Artikel ini menggunakan metodologi feminis dengan menggunakan wawancara dan studi literatur sebagai metode pencari data. Penelitian ini menunjukkan bahwa kepemimpinan di PTKIN masih didominasi oleh laki-laki karena masih kuatnya budaya patriarki. Hanya ada tujuh rector perempuan pada 58 PTKIN di Indonesia. Berdasarkan penemuan ini, penafsiran baru tentang Al-Qur’an yang ramah terhadap perempuan perlu dipromosikan dan kebijkan yang netral gender yang ada sekarang ini tentang seleksi rector di PTKIN perlu direvisi menjadi kebijakan afirmatif untuk memberikan ruang yang lebih luas bagi kepemimpinan perempuan, agar dapat mencapai Planet 50-50 pada tahun 2030.]